2017
DOI: 10.1002/2017gl072797
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a detectable lunar nanodust exosphere during a search with LRO's LAMP UV imaging spectrograph

Abstract: The Lyman‐Alpha Mapping Project (LAMP) UV spectrograph on board the Lunar Reconnaissance Orbiter (LRO) performed a campaign to observe the Moon's nanodust exosphere, evidence for which was provided by the Lunar Atmosphere and Dust Environment Explorer (LADEE) Ultraviolet and Visible Spectrometer (UVS) during the 2014 Quadrantid meteoroid stream. These LADEE/UVS observations were consistent with a nanodust exosphere modulated by meteoroid impacts. LRO performed off‐nadir maneuvers around the peak of the 2016 Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…They hypothesized that a spatially and temporally variable nanodust exosphere may exist on the Moon that is modulated by meteor showers. In contrast, Grava et al (2017) found no evidence for a detectable nanodust exosphere in a series of UV spectral observations taken with LAMP during the 2016 Quadrantids. The resulting nanodust line-of-sight column density limits were ∼10-100 times lower than the densities estimated by Wooden et al (2016).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…They hypothesized that a spatially and temporally variable nanodust exosphere may exist on the Moon that is modulated by meteor showers. In contrast, Grava et al (2017) found no evidence for a detectable nanodust exosphere in a series of UV spectral observations taken with LAMP during the 2016 Quadrantids. The resulting nanodust line-of-sight column density limits were ∼10-100 times lower than the densities estimated by Wooden et al (2016).…”
Section: Introductionmentioning
confidence: 78%
“…In contrast, Grava et al. () found no evidence for a detectable nanodust exosphere in a series of UV spectral observations taken with LAMP during the 2016 Quadrantids. The resulting nanodust line‐of‐sight column density limits were ∼10–100 times lower than the densities estimated by Wooden et al.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, in order to mitigate the lunar dust-related problems, provide substantial guidance for the planning of future lunar exploration even extraterrestrial settlement constructions, and offer valuable information for understanding lunar atmospheric evolution, in situ measurement of dust deposition on the lunar surface is the first step for achieving these purposes. To date, however, the reports about in situ measurements of dust on the lunar near surface are comparatively few (Berg et al, 1976;Grün & Horányi, 2013;O'Brien, 2011) even though some studies were executed from lunar orbits (Feldman et al, 2014;Glenar et al, 2014;Grava et al, 2017;Horányi et al, 2015;Szalay & Horányi, 2015b;Wooden et al, 2016 Here, we report in situ measurement results obtained by one sensor of LDD-sticky quartz crystal microbalance (SQCM), which was installed in a temperature-controlled cabinet mounted on the front-left corner of the CE-3 lander and devoted to detect the lunar dust principally induced by natural factors in each lunar daytime during 1-year-mission duration. The temperature-controlled cabinet was opened in sunrise period about a solar elevation of 20°and closed in sunset period about a solar elevation of 20°in each lunar daytime in order to make sure all the scientific instruments can survive and operate over the harsh low-temperature lunar night.…”
Section: 1029/2019je006054mentioning
confidence: 99%
“…Thus, in order to mitigate the lunar dust‐related problems, provide substantial guidance for the planning of future lunar exploration even extraterrestrial settlement constructions, and offer valuable information for understanding lunar atmospheric evolution, in situ measurement of dust deposition on the lunar surface is the first step for achieving these purposes. To date, however, the reports about in situ measurements of dust on the lunar near surface are comparatively few (Berg et al, ; Grün & Horányi, ; O'Brien, ) even though some studies were executed from lunar orbits (Feldman et al, ; Glenar et al, ; Grava et al, ; Horányi et al, ; Szalay & Horányi, ; Wooden et al, ). On 14 December 2013 at 21:11 (UTC + 8), Chang'E‐3 (CE‐3) spacecraft, the first visitor from China soft‐landing on the Moon surface, successfully touched down at 44.12°N, 19.51°W on the Moon (Fa et al, )—a region that was neglected by previous expeditions, which carried, among other instruments, one lunar dust detector (LDD), providing an unique opportunity to learn about the lunar dust deposition in the northern Mare Imbrium.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide more insights into the actual lunar dust environment, it is necessary to make reliable in situ dust explorations on the lunar surface. To date, however, the reports about in situ investigations of lunar dust on the moon surface are relatively few (Grün & Horányi, 2013; Li et al, 2019; O'Brien, 2009; O'Brien & Hollick, 2015; Yan et al, 2019) in contrast with multiple searches carried out from lunar orbit over the past three decades (Barker et al, 2019; Feldman et al, 2014; Glenar et al, 2011, 2014; Grava et al, 2017; Horányi et al, 2015; Iglseder et al, 1996; Szalay & Horányi, 2015; Wooden et al, 2016; Zook & McCoy, 1991). Unlike the orbital investigations, in situ measurements made with lunar dust detector on the lunar surface can provide essential ground‐truth data to validate or correct the results obtained from lunar orbiters as the latter significantly depend on the size and location of the putative lunar dust particles in most cases.…”
Section: Introductionmentioning
confidence: 99%